Mallard–Black Duck Hybridization and Population Genetic Structure in North Carolina. Issue 6 (20th June 2021) - Lawson, Daniel M.; Williams, Christopher K.; Lavretsky, Philip; Howell, Douglas L.; Fuller, Joseph C.
ABSTRACT: North Carolina, USA, represents the southern extent of the American black duck's ( Anas rubripes ) breeding range. Mallards ( A. platyrhynchos ) are present on the breeding grounds of the American black duck and hybridization is observed between these species; therefore, we assessed the genetic integrity, hybridization rates, and population structure of this local breeding population. We extracted genomic and mitochondrial DNA from chorioallantoic membranes and contour feathers from monitored black duck nests. We then prepared the extracted DNA for analysis using high‐throughput DNA sequencing methods (ddRAD‐seq). First, we assessed nuclear and mitochondrial population structure, genetic diversity, and differentiation across samples from North Carolina, and compared them against 199 genetically vetted mallards, black ducks, and mallard × black duck hybrids that served as genetic references. Next, we tested for parentage and sibling relationship and overall relatedness of black ducks in North Carolina. We recovered strong population structure and high co‐ancestry across genetic markers due to interrelatedness among sampled nests in North Carolina and concluded that black ducks have been locally breeding in this area for a prolonged period of time. Despite a high level of interrelatedness among our samples, nucleotide diversity was similar to the reference continental black duck population, suggesting little effect of genetic drift, including inbreeding. Additionally, we conclude that molecular diversity of black ducks in North Carolina is maintained at reference population levels through the influx of genetic material from unrelated, migrating male black ducks. Finally, we report a hybridization level of 47.5%, covering 3 filial generations. Of identified hybrids, 54.7% and 53% were the direct result of interbreeding between black ducks and captive‐reared or wild mallards, respectively. We conclude that because of high rates of interspecific hybridization and successive backcrossing events, introgression from wild and feral mallards is occurring into this population of breeding black ducks and requires careful consideration in future management efforts. © 2021 The Wildlife Society. : High rates of interspecific hybridization, successive backcrossing events, and introgression from wild and feral mallards is occurring into the breeding American black duck population, North Carolina, USA, 2017–2018, that requires careful consideration in future conservation efforts. We contend that conservation and management efforts of American black ducks in North Carolina and the Atlantic flyway, would benefit from heavier restrictions on captive‐reared mallard stocking practices on shooting preserves.